1996
DOI: 10.1111/j.1540-8191.1996.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Left Ventriculectomy to Improve Left Ventricular Function in End-Stage Heart Disease

Abstract: We present a case of a 34-year-old male with dilated cardiomyopathy in whom we performed a new surgical procedure; Le., ventricular volume reduction to improve function. This initial human experience was preceded by a series of ten sheep in which we demonstrated that by enlarging the left ventricle (LV), the ejection fraction was reduced, and by restoring normal diameter, the LV function returned to normal. (J Card Surg 7996;77:96-97)Over the last 45 years, we have observed that all animal hearts have the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
169
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(180 citation statements)
references
References 2 publications
4
169
0
7
Order By: Relevance
“…Without doubt, part of the expressed concept in this surgical reconstruction technique of the left ventricle represents a direct application of the ideas developed in the weekly works of Brazilian authors, JATENE [1] and BATISTA et al [24].…”
Section: Commentsmentioning
confidence: 99%
“…Without doubt, part of the expressed concept in this surgical reconstruction technique of the left ventricle represents a direct application of the ideas developed in the weekly works of Brazilian authors, JATENE [1] and BATISTA et al [24].…”
Section: Commentsmentioning
confidence: 99%
“…However, there is a limited supply of hearts available for transplantation. As a surgical therapeutic option for the treatment of patients with end-stage DCM, PLV was first reported by Batista et al in 1996 [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the original Batista procedure [1], the posterolateral wall of the left ventricle is widely resected. Some patients undergoing the procedure lose the coronary arteries, papillary muscles and mitral complex due to PVL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pioneering work has been undertaken by Dr R. Batista and has examined the aberration in left ventricular mass/volume relationship in patients with cardiomyopathy. Re-normalizing this relationship by reducing left ventricular chamber volume surgically (the Batista procedure) was proposed, aiming at reducing wall tension and improving myocardial contractility [3]. Early experience has shown that this procedure results in a significant improvement in left ventricular contractility and functional class in many patients [4,5].…”
mentioning
confidence: 99%